1970
DOI: 10.3329/cardio.v3i1.6427
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track Cardiac Surgery in Children: Feasibility in Bangladeshi Setting

Abstract: Background: Fast-track recovery protocols in cardiac surgery is gaining worldwide popularity and have contributed to significant reductions in the postoperative hospital stay and cost without any increase in postoperative mortality and morbidity. The aim of this study was to find out the feasibility of fast track paediatric cardiac surgery in Bangladeshi setting. Method: It was a prospective study conducted in National Institute of Cardio-vascular Diseases, Dhaka, from July 2009 to June 2010. All patients, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Arrhythmia was previously reported in one study with wound sepsis being reported fairly more commonly but with nonfatal results and with no obvious link to OTE . Our mean length of stay in the CICU is also comparable with other studies that show a reduced length of stay between 1 and 3 days . Alghamdi et al.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Arrhythmia was previously reported in one study with wound sepsis being reported fairly more commonly but with nonfatal results and with no obvious link to OTE . Our mean length of stay in the CICU is also comparable with other studies that show a reduced length of stay between 1 and 3 days . Alghamdi et al.…”
Section: Discussionsupporting
confidence: 87%
“…11,15 Our mean length of stay in the CICU is also comparable with other studies that show a reduced length of stay between 1 and 3 days. [6][7][8]19,21 Alghamdi et al showed in a systematic review and meta-analysis a reduction in length of ICU and hospital stay without adverse effects on respiratory morbidity or overall mortality. Early extubation in pediatric congenital cardiac surgery from a center in a developing country is desirable due to the fact that specialized intensive care facilities are in short supply, and saving a few hours on the ventilator in the postoperative period may lead to significant cost savings as shown in two prospective trials and a review by Mittnacht et al 11,21,22 Heinle et al documented a cost reduction of $21 108 ± $14 941 vs. $31 608 ± $9861 ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimizing the length of hospital stay was therefore hoped to reduce costs for the family. Conversely, a study from Bangladesh described that lack of follow‐up services outside the city led patients in the ‘fast track’ pathway to stay near the hospital for at least a week post‐discharge [42].…”
Section: Resultsmentioning
confidence: 99%
“…Cooperation and good team communication were reported as facilitators to implementation [25, 27]. High demand for surgery, performance indicators and the need for efficient use of limited resources created tension for change away from existing care [25, 42, 50]. Two Indian studies conducted in specialized hospitals acknowledged that their existing resources were not representative of most LMIC institutions, where resource constraints could act as a barrier [30, 34].…”
Section: Resultsmentioning
confidence: 99%